Characterization of V‐set and immunoglobulin domain containing 1 exerting a tumor suppressor function in gastric, lung, and esophageal cancer cells. Issue 8 (29th July 2017) - Inoue, Yusuke; Matsuura, Shun; Yoshimura, Katsuhiro; Iwashita, Yuji; Kahyo, Tomoaki; Kawase, Akikazu; Tanahashi, Masayuki; Maeda, Matsuyoshi; Ogawa, Hiroshi; Inui, Naoki; Funai, Kazuhito; Shinmura, Kazuya; et al.
Abstract : V‐set and immunoglobulin domain containing 1 (VSIG1) is a newly discovered member of the immunoglobulin superfamily of proteins, expressed in normal stomach and testis. In cancers, however, the clinical and biological roles of VSIG1 remain unknown. Here we investigated VSIG1 expression in 11 cancers and assessed the prognostic roles of VSIG1 in patients with gastric cancer (GC) ( n = 362) and non‐small‐cell lung cancer ( n = 650). V‐set and immunoglobulin domain containing 1 was downregulated in 60.5% of GC specimens, and high VSIG1 expression was identified as an independent favorable prognostic factor for overall survival in GC patients (hazard ratio, 0.58; 95% confidence interval, 0.35–0.96). Among lung adenocarcinomas ( n = 428), VSIG1 was significantly and inversely associated with thyroid transcription factor 1 expression and was frequently expressed in the invasive mucinous subtype (17 of 19, 89.5%). In addition, VSIG1 was expressed in a subset of pancreatic, ovarian, and prostate cancers. The variant 2 VSIG1 transcript was the dominant form in these tissues and cancer cells. Introduction of VSIG1 significantly reduced the proliferative ability of MKN1 and MKN28 GC cells and H1299 lung cancer cells and downregulated cell migration of these cells, as well as of KYSE150, an esophageal cancer cell line. Cell invasion of MKN1, MKN28, and KYSE150 cells was also reduced by VSIG1 introduction. In vitro characterization revealed that VSIG1 forms homodimers through homophilic cis ‐interactions but not through homophilic trans ‐interactions. These results suggest that VSIG1 possesses tumor suppressive functions that are translated into favorable prognosis of VSIG1‐expressing GC patients. Abstract : This is the first detailed characterization of VSIG1 in terms of clinical, pathological, and biological relevance. VSIG1 is expressed in mucinous neoplasms of the stomach, lung, pancreas, and ovary, and is a tumor suppressive marker to predict the prognosis of patients with gastric cancer.